MEMBUMIKAN TEOLOGI ISLAM DALAM KEHIDUPAN BERAGAMA (PERSPEKTIF M ARKOUN) - Zulkarnain, Zulkarnain (Studia Sosia Religia, 2023)
Point inertia classical Islamic theology thought would appear in the realm of reality if the thought process faced with the reality or the reality of empirical social human life is always growing and developing in line with the growth of science and technology. Mohammed Arkoun is Algerian intellectuals who tried to reread the building of Islamic thought in comprehensive both involving thought kalam (theology), Sufism, jurisprudence, ethics and interpretation. In the Indonesian context, Arkoun thought first recognized in 1987 in a discussion on Empathy Foundation. Muhammad Nasir Tamara, who introduced first by writing an article entitled Mohammed Arkoun and Applied Islamology. In some writings about modernity, Arkoun does not explicitly formulate the constraints of modernity, let alone challenge under him. According to Arkoun, modernity can be divided into two groups, namely, modernity "material" and modernity "intellectual" or "cultural". The former means that much progress has occurred in the outer frame of the human form, while the latter includes the methods, analysis tools, and intellectual siakp which gives the ability to better understand the reality. One anxiety Arkoun against Islamic theological thought is the separation between Islam and Islam actual or conceptual separation between theory and practice which he said is the legacy of Descartes. Grounding Islamic theology in the context of modern life does require accurate strategies and methodologies. Arkoun effort in the context of building reconstruction of Islamic theological thought is one of the strategies